PENGARUH KOMPETENSI PROFESIONAL GURU DAN FASILITAS BELAJAR TERHADAP MUTU PENDIDIKAN DI SMK PK BIM JOMBANG - Kartiningsih, Vita Dewi (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
The quality of education is a benchmark for the success of educational institutions in producing the quality of students. It can be seen that in order to produce quality students, they must have professional teachers who are able to carry out quality learning, and have complete and adequate learning facilities. What is the influence of teacher professional competence and learning facilities on the quality of education at SMK PK BIM Jombang, and which one has more influence on teacher professional competence and learning facilities on the quality of education at SMK PK BIM Jombang. The samples in this research were students of SMK PK BIM Jombang. In this research, the sampling technique is proportional random sampling. The data collection was through a questionnaire distributed directly to 97 respondents. The results of this research show that teacher professional competence and learning facilities have a positive and significant effect on the quality of education, both partially and simultaneously. In this research, there is a partial influence between teacher professional competence on the quality of education as seen from the results of the t-test which shows that the tcount value is 2.844 > ttable of 1.986, while the influence is 26.8%. And there is an influence of learning facilities on the quality of education, namely the value obtained is tcount 6,768 > ttable 1.986, while the influence is 63.8%. And found the results of simultaneous influence calculations, namely 76.9%.